The prerogative of confusion: pink film and the eroticization of pain, flux and disorientation. (11th March 2019) - Zahlten, Alexander
Abstract: This essay explores the specific aesthetics and politics of pink film, a popular soft-sex film genre that exerted immense influence on the history of Japanese cinema after the 1960s. It argues that the explosive success of pink film – making up nearly half of Japanese film production within just three years of its first appearance – was due to its ability to mix, contain and express the contradictions of postwar and high-growth Japan. Focusing on the strategy of mixing live theatrical performances with film screenings, but also pointing out other aesthetic strategies such as part-colour films, the essay describes how on the levels of its material aesthetics, carefully calibrated but highly problematic identificatory strategies, and its interaction with live performance, pink film deliberately and successfully performed a politics of confusion. It concludes that this resulted in the establishment of a homosocial intimate public that perceived itself as oppositional but was just as much a site of the development of exactly what it attempted to resist – the high-growth system of the 1960s with its reorganization of labour and capture of gendered audiences.